2021
DOI: 10.1021/acssuschemeng.1c01187
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Multiple-Step Integration Strategy for Efficient Fixation of CO2 into Chain Carbonates by Azolide Anions Poly(ionic liquid)s

Abstract: The multiple-step transformation of CO2 greatly enriches the diversity and value of products and provides more possibilities for the sustainable development of green chemistry. However, it puts forward stricter requirements for the versatility of catalysts. A series of basic porous ionic polymers incorporating azolide anions (BA-PILs) were facilely synthesized via radical polymerization followed by a successive ion-exchange strategy. A one-pot multiple-step integration strategy coupling cycloaddition and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…44,45 Poly(ionic liquid)s (PILs), as a class of functional materials with tunable catalytic active sites and designable structure, and satisfactory physicochemical property, has spurred great interest in the cycloaddition of CO 2 to epoxides. 46,47 Several studies have reported that the nucleophile properties of PILs can effectively catalyze the cycloaddition of CO 2 to cyclic carbonates under relatively mild conditions. 48,49 However, the PILs usually exhibit dissatised CO 2 cycloaddition performance because of the lack of a well-developed pore structure that allows insufficient exposure of the active site.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 Poly(ionic liquid)s (PILs), as a class of functional materials with tunable catalytic active sites and designable structure, and satisfactory physicochemical property, has spurred great interest in the cycloaddition of CO 2 to epoxides. 46,47 Several studies have reported that the nucleophile properties of PILs can effectively catalyze the cycloaddition of CO 2 to cyclic carbonates under relatively mild conditions. 48,49 However, the PILs usually exhibit dissatised CO 2 cycloaddition performance because of the lack of a well-developed pore structure that allows insufficient exposure of the active site.…”
Section: Introductionmentioning
confidence: 99%
“…ALIE is an excellent method to discuss the possible area which would react with the electricity-rich group. In these reactions mentioned above, the BH 3 group was the most electricity-rich group, which could react with positively charged regions, such as the N–H in the triazole or the tetrazole, which was quantified as displayed by the maximum points of the ESP mapping [ 31 , 32 , 33 , 34 ]. As shown in Figure 14 , the area surrounding N–H in the tetrazole obtained the maximum value of the ESP mapping, which might be the most possible region among these azoles to react with the BH 3 group in the 1-methylimidazole borane complex.…”
Section: Resultsmentioning
confidence: 99%
“…These PILs with moderate surface area and IL content were used as the heterogeneous catalysts in the CO 2 cycloaddition, exhibiting high yields under relatively mild conditions. 106,116 The wettability of the porous PILs can be adjusted by varying the linkers. DVB was the most frequently used linker with a hydrophobic property, while hydrophilic EGDMA was used to increase the hydrophilicity of porous PILs.…”
Section: One-step Synthesis Of Porous Pilsmentioning
confidence: 99%